A SUCCESSFUL TREATMENT OF INTRAVITREAL MOXIFLOXACIN INJECTION IN ACUTE POST-CATARACT SURGERY ENDOPHTHALMITIS: A CASE REPORT: Poster Presentation - Case Report - General practitioner - Ardityastiti, Khairani Azizah; Wibawaty, Halida (Majalah Oftalmologi Indonesia, 2023)
Introduction : Endophthalmitis is a severe form of ocular inflammation and one of the most dreaded cataract surgery complications which may lead to loss of vision. Post-cataract surgery endophthalmitis is a serious complication that occurs when infecting organisms invade the posterior segment of the eye during the time of surgery. Currently, intravitreal injection of vancomycin along with ceftazidime is the first-line treatment, but another study showed a good result of intravitreal moxifloxacin injection in patients with Postoperative endophthalmitis. Case Illustration : We reported a 59-year-old woman presented with blurred vision, redness, and pain in the left eye 4 days after phacoemulsification. Visual acuity of LE was hand movement and anterior segment examination found that there was a conjunctival and pericorneal injection, corneal edema, cells, and anterior chamber fibrin formation. Ultrasonography examination showed severe levels of debris in the vitreous humor. Patient was diagnosed with acute post-cataract surgery endophthalmitis and received an intravitreal moxifloxacin injection. Fortunately, one week after that injection, there wasa good result in the patient’s eye condition. Visual acuity of LE improved to 0,1 and the patient planned to receive the second moxifloxacin injection to get the best possible results. Discussion : Moxifloxacin expresses broad-spectrum microbial coverage with a very good diffusion and low adverse effects. Moxifloxacin also has a better penetration ability into inflamed ocular tissue than all other antibiotics. Based on that, other studies said that intravitreal moxifloxacin can replace vancomycin and ceftazidime combinations for the treatment of ocular infections. Conclusion : Intravitreal moxifloxacin injections have a good result in acute post-cataract surgery endophthalmitis.